2019
DOI: 10.1111/1753-6405.12859
|View full text |Cite
|
Sign up to set email alerts
|

Men’s work, women’s work and suicide: a retrospective mortality study in Australia

Abstract: Objectives: This research sought to investigate the influence of being a in male‐dominated occupation on suicide. Methods: A population‐level retrospective mortality study was conducted over the period 2001 to 2015. Data from the Australian Census and the National Coronial Information System were combined. Negative binomial regression was used to assess the relationship between occupational gender ratio and suicide rates, controlling for age, socioeconomic status and year of death. Probabilistic sensitivity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…In higher-income countries, the incidence of male suicide is three to four times greater than that of female suicide, due in part to the fact that men use more lethal means, such as hanging, while women use methods such as drug overdose, which is less likely to cause death, and women are also more likely to seek medical attention after intentional self-harm [ 7 ]. The relevant factors driving these global and sex-based differences in the choice and prevalence of suicide methods appear to be physical and cognitive availability, lethality and socio-cultural acceptability [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In higher-income countries, the incidence of male suicide is three to four times greater than that of female suicide, due in part to the fact that men use more lethal means, such as hanging, while women use methods such as drug overdose, which is less likely to cause death, and women are also more likely to seek medical attention after intentional self-harm [ 7 ]. The relevant factors driving these global and sex-based differences in the choice and prevalence of suicide methods appear to be physical and cognitive availability, lethality and socio-cultural acceptability [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicating that men working in male-dominated occupations have poorer health literacy must be considered in the context of previous research that has demonstrated the effects of occupational gender ratio on mental health (Milner, King, LaMontagne, et al, 2018), suicide (Milner and King, 2019), and mental health service use (Milner, King, et al, 2018a; Milner, Scovelle, et al, 2018b). Other studies have suggested that health literacy is a mediator of the relationship between socioeconomic status and health outcomes (Stormacq et al, 2019).…”
Section: Discussionmentioning
confidence: 60%
“…The evidence substantiating this is extensive and far reaching. In Australia, evidence from retrospective mortality studies (Milner et al, 2014; Milner and King, 2019) and a systematic review (Milner et al, 2013) has indicated that males employed in male-dominated occupations are at an elevated risk of suicide. Across the world, the construction industry is male dominated, and cohort data from male workers in the German construction industry identified an increased risk of fatal injuries and accidents compared to that for other workers (Arndt et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Perceived racism has also been linked to suicidality, with a mediating role of depression and moderating role of religiosity 10 . Male‐dominated industries such as the construction industry have also been linked to higher suicide rates (especially for men), 11 with research showing that those in the most unskilled occupations are most at risk within the construction industry 12 . While economic crises are associated with a spike in the suicide rate, 16 research from Spain showed that this trend is more pronounced for those aged 35 to 54 years and unemployed males 13 .…”
Section: Framing Suicide Preventionmentioning
confidence: 99%